Rancang Bangun Sistem Penyewaan Lapangan Badminton Berbasis Website Dengan Metode Rapid Application Development (Studi Kasus: Gor Kunir Pondok Cabe) - Ronald Simatupang; Dani (CV. Shofanah Media Berkah, 2023)
The Kunir sports facility building is a business unit that rents badminton venues where the rental process still uses the conventional method of ordering by arriving directly at the venue or ordering via telephone, from these problems, the author took the initiative to develop a data system for the rental of website-based sports facilities with PHP &xamp; MySQL to help the operational activities of tenant data collection. With the existence of this data system, it can make it easier for tenants and landlords to obtain accurate information, such as existing and non-available field data, the procedure used in this research is Rapid Application Development which consists of 3 stages: Requirements Planning, RAD Design Workshop, and Implementation, the result of the system that has been made is in the form of a field rental system that can make it easier for customers to rent fields and make it easier for owners to carry out tenant data collection and report generation.